2004
DOI: 10.1519/14523.1
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness Profile of Army ROTC Cadets

Abstract: One role of Army Reserved Officer's Training Corps (ROTC) programs is to physically prepare cadets for the demands of a military career. Cadets participate in physical training 3 days per week as part of their military science curriculum. Limited research has been conducted on the fitness level of ROTC cadets; therefore, the purpose of this study was to profile the physical fitness status of a cadre of ROTC cadets. Forty-three cadets (30 men and 13 women) performed Army Physical Fitness Test (APFT) assessments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 0 publications
1
27
1
1
Order By: Relevance
“…The gold standard of dynamic strength is the highest weight that can be lifted (1-RM) and bench-press performances have proved to be significantly correlated to specific fire-fighting performances [36]. In this study only volunteers showed 1RM values comparable to army recruits [40], being slightly above average (around the 60th percentile) for age and gender [41]. On the other hand, the significantly lower values of the novice recruits (between the 40th and 50th percentiles) indicate that they need further training to improve their upper limb strength.…”
Section: Discussionmentioning
confidence: 69%
“…The gold standard of dynamic strength is the highest weight that can be lifted (1-RM) and bench-press performances have proved to be significantly correlated to specific fire-fighting performances [36]. In this study only volunteers showed 1RM values comparable to army recruits [40], being slightly above average (around the 60th percentile) for age and gender [41]. On the other hand, the significantly lower values of the novice recruits (between the 40th and 50th percentiles) indicate that they need further training to improve their upper limb strength.…”
Section: Discussionmentioning
confidence: 69%
“…Soldiers are required to perform numerous tasks involving an extensive degree of physical effort throughout their military career. [7][8][9][10] While soldiers demonstrate to have a significant amount of both strength and endurance, they often are involuntarily forfeiting efficient movements to perform high level activities specific to their military obligations. Consequently, they are adding fitness to their dysfunction.…”
Section: Contentsmentioning
confidence: 99%
“…Many resources have established the need for both cardiovascular and muscular strength and endurance to be able to perform specific military tasks successfully. 7,9,10,30 Soldiers are required to be physically fit in order to be able to perform war time duties therefore, the importance of objective measurements of a soldier's physical capacity has constantly been an important concept for the US Army. Currently, the Army only has one standardized measurement to evaluate the physical capabilities for soldiers across the service.…”
Section: Army Physical Fitness Testmentioning
confidence: 99%
See 2 more Smart Citations